Fetal Brain Biometric Measurements on 3D Super-Resolution Reconstructed T2-Weighted MRI: An Intra- and Inter-observer Agreement Study - Khawam, Marie; de Dumast, Priscille; Deman, Pierre; Kebiri, Hamza; Yu, Thomas; Tourbier, Sébastien; Lajous, Hélène; Hagmann, Patric; Maeder, Philippe; Thiran, Jean-Philippe; Meuli, Reto; Dunet, Vincent; et al. (Frontiers in Pediatrics, 2021)
We present the comparison of 2-dimensional (2D) fetal brain biometry on Magnetic Resonance (MR) images using orthogonal 2D T2-weighted sequences (T2WS) versus one 3D super-resolution (SR) reconstructed volume, and evaluation of the level of confidence and concordance between an experienced pediatric radiologist (obs1) and a junior radiologist (obs2). Twenty-ﬁve normal fetal brain MRI scans (18-34 weeks of gestation) including orthogonal 3-mm thick T2WS, were analyzed retrospectively. One 3D SR volume was reconstructed per subject based on multiple series of T2WS. The two observers performed 11 2D biometric measurements (specifying their level of confidence) on T2WS and SR volumes. Measurements were compared using the paired Wilcoxon rank sum test between observers for each dataset (T2WS and SR) and between T2WS and SR for each observer. Bland-Altman plots were used to assess the agreement between each pair of measurements. Measurements were made with low conﬁdence in 3 subjects by obs1 and in 11 subjects for obs2 (mostly concerning the length of the corpus callosum on T2WS). Inter-rater intra-dataset comparisons showed no signiﬁcant difference (p>0.05), except for brain axial biparietal diameter (BIP) on T2WS, and for brain and skull coronal BIP and coronal transverse cerebellar diameter (DTC) on SR. None of them remained significant after multiple comparisons correction. Inter-dataset intra-rater comparisons showed statistical differences in brain axial and coronal BIP for both observers, skull coronal BIP for obs1, axial and coronal DTC for obs2. After correction for multiple comparisons, only axial brain BIP remained signiﬁcantly different, but differences were small (2.95±1.73 mm). SR allows similar fetal brain biometry as compared to using the conventional T2WS, while improving the level of confidence in the measurements and using a single reconstructed volume.